Regulation of PKCβ levels and autophagy by PML is essential for high-glucose-dependent mesenchymal stem cell adipogenesis - Morganti, Claudia; Missiroli, Sonia; Lebiedzinska-Arciszewska, Magdalena; Ferroni, Letizia; Morganti, Lucia; Perrone, Mariasole; Ramaccini, Daniela; Occhionorelli, Savino; Zavan, Barbara; Wieckowski, Mariusz R.; Giorgi, Carlotta (International Journal of Obesity, 2019)
Background/Objectives Obesity is a complex disease characterized by the accumulation of excess body fat, which is caused by an increase in adipose cell size and number. The major source of adipocytes comes from mesenchymal stem cells (MSCs), although their roles in obesity remain unclear. An understanding of the mechanisms, regulation, and outcomes of adipogenesis is crucial for the development of new treatments for obesity-related diseases. Recently an unexpected role for the tumor suppressor promyelocytic leukemia protein (PML) in hematopoietic stem cell biology and metabolism regulation has come to light, but its role in MSC biology remains unknown. Here, we investigated the molecular pathway underlying the role of PML in the control of adipogenic MSC differentiation. Subjects/Methods Muscle-derived stem cells (MDSCs) and adipose-derived stem cells (ADSCs) obtained from mice and voluntary patients (as a source of MSCs) were cultured in the presence of high glucose (HG) concentration, a nutrient stress condition known to promote MSCs differentiation into mature adipocytes and the adipogenic potential of PML was assessed. Results PML is essential for a correct HG-dependent adipogenic differentiation, and the enhancement of PML levels is fundamental during adipogenesis. Increased PML expression enables the upregulation of protein kinase Cβ (PKCβ), which, in turn, by controlling autophagy levels permits an increase in peroxisome proliferator-activated receptor γ (PPARγ) that leads the adipogenic differentiation. Therefore, genetic and pharmacological depletion of PML prevents PKCβ expression, and by increasing autophagy levels, impairs the MSCs adipogenic differentiation. Human ADSCs isolated from overweight patients displayed increased PML and PKCβ levels compared to those found in normal weight individuals, indicating that the PML-PKCβ pathway is directly involved in the enhancement of adipogenesis and human metabolism. Conclusions The new link found among PML, PKCβ, and autophagy opens new therapeutic avenues for diseases characterized by an imbalance in the MSCs differentiation process, such as metabolic syndromes and cancer.